STRATEGI PENGEMBANGAN SUBSEKTOR PERIKANAN DARAT SEBAGAI USAHA MENINGKATKAN PERTUMBUHAN EKONOMI KABUPATEN BENGKULU TENGAH PROVINSI BENGKULU - Dian Mardiati Sari; Rina Trisna Yanti (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2021)
The objective of this research is to analyze the potential of aquaculture subsector, knowing the prospsect of aquaculture subsector development, and designing appropriate strategies for the development of aquaculture subsector in Central Bengkulu Reqency. This research is explanatory research. Sample was take by purposive sampling and accidental sampling counted 20 samples. Data collected by documentation and questionnaire. Data analyzed by Descriptive analyzes were used to analyze the potential and prospects of fisheries and SWOT analysis is used to determine the aquaculture sub-sector development strategy in Central Bengkulu Regency. From result of data analysis and research showed Central Bengkulu has the potential to develop aquaculture subsector. Aquaculture subcector in Central Bengkulu Regency has prospects to develop more optimal, where new production reached 22.17 % of the existing production prospect so that intensification of land productivity so as to achieve producticn 14,761.60 tonnes/year in the existing cultivation area. To achieve the production, aquaculturecan also provide employment is 13.581 people, aquaculture sub-sector development strategy in Central Bengkulu district conducted is a progressive strategy, which is done optimizing the development of aquaculture subsector.